2020
DOI: 10.1109/access.2020.2991261
|View full text |Cite
|
Sign up to set email alerts
|

Blockchain-Based Decentralized Reverse Bidding in Fog Computing

Abstract: Fog computing systems are designed to provide localized computation, storage, and communication services in close proximity to the endpoint mobile and IoT devices. Fog service providers typically monetize their service usage via centralized payment mechanisms in unverifiable and non-transparent manner. Therefore, there exists a need for a trust-enabling payment mechanism whereby fog service providers should be incentivized or penalized based upon the continuous feedback from endpoint devices. We propose a dece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…The limitation of this work is that a user may get a less efficient service provider during allocation (alteration in providers' wealth rank), but it is required to maintain competition in the market, to reduce bidder drop problem and to overcome cloud market stagnation. Future work is intended to be more focused on designing fair mechanisms using some different approaches such as blockchain [66], feedback based fairness [34,67], etc. A generalized architectural framework for reverse auction-based market would definitely be helpful for the researchers and the academicians to design fair mechanisms in a more complex fog/edge environment [35].…”
Section: Discussionmentioning
confidence: 99%
“…The limitation of this work is that a user may get a less efficient service provider during allocation (alteration in providers' wealth rank), but it is required to maintain competition in the market, to reduce bidder drop problem and to overcome cloud market stagnation. Future work is intended to be more focused on designing fair mechanisms using some different approaches such as blockchain [66], feedback based fairness [34,67], etc. A generalized architectural framework for reverse auction-based market would definitely be helpful for the researchers and the academicians to design fair mechanisms in a more complex fog/edge environment [35].…”
Section: Discussionmentioning
confidence: 99%
“…It integrates a truthful double auction and a bidding language to match highly heterogeneous edge resources with different service requests. Debe et al [124] demonstrated a blockchainbased reverse auction solution for public fog service allocation. Yu et al [125] also leveraged the reverse auction model and presented a blockchain-based edge crowdsourcing service system.…”
Section: Service Allocationmentioning
confidence: 99%
“…5) Debe et al [45] implemented a reputation-based mechanism using a blockchain to identify the reputation of a fog node either to distribute incentives or to penalize them for bad behaviour.…”
Section: Author Purpose Synopsismentioning
confidence: 99%